Power sharing and voltage compensation modeling using adaptive virtual impedance-based predictive control in islanded microgrid - Khan, Mubashir Hayat (2023)
In microgrid’s islanded mode of operation, the precise power sharing is an immensely critical challenge when there is a difference in line impedance of the DG inverters connected in parallel. The existing control strategies in parallel connected inverter-based microgrid power sharing issues, voltage compensation at point of common coupling (PCC) and circulating current among connected inverters in mismatched feeder impedance case need to be addressed. This project aimed to develop decentralised power sharing and voltage compensation modelling using the predictive control scheme for an islanded microgrid structure with two Voltage Source Converters (VSCs). This mismatched impedance was nullified by using the adaptive virtual impedance (AVI) control. The finite control set–model predictive control (FCS-MPC) strategy was used to replace the pulse-width modulation (PWM) strategy in order to have fast response, which had the benefit of power sharing among the VSCs, while compensating for the rated voltage at the PCC due to load changing. The AVI was used to generate the reference voltage, which responded to the values of the impedance mismatch by utilising the derivative terms for the FCS-MPC for faster tracking response and minimum tracking error when the load changed rapidly. The AVI-based predictive control scheme was compared with the conventional and static virtual impedance (SVI) methods based on the simulation results obtained through MATLAB/Simulink software. From the results, the power sharing accuracy for the connected loads for the proposed AVI-based predictive control scheme improved by 99%. The voltage error for the compensation at PCC was 0.01% under the AVI-based predictive control scheme, 1.92 % under the SVI-based control scheme and 0.72 % under the conventional control scheme. The circulating current was suppressed up to 0.047 A under the AVI-based predictive control scheme with the condition of mismatched line impedances. The AVI-based predictive control scheme was able to enhance power sharing performance and simultaneously maintain the voltage magnitude at the PCC effectively when the loads changed